An anonymous pre-Linnaean herbarium among the "treasures" of the "Civica and A. Ursino Recupero" joint library of Catania (Italy). (1st November 2020) - Costa, R. M. S.; Pavone, P.; Carbonaro, R. A.; Pulvirenti, S.
Abstract: A study of an anonymous pre-Linnaean herbarium, currently kept in the "Civica and A. Ursino Recupero" joint library of Catania (Italy) has been carried out. The volume examined consists of 86 unnumbered pages. It is made up of 121 specimens (currently four samples are missing), all belonging to Angiosperms. The samples are not all in good condition; however, it was possible to determine most of them (86%) up to species level. Most of the taxa are made up of alien plants (20.62%) of African and American origin. A series of concordant clues leads us to conjecture that the herbarium was produced by Antonio Bonanno (a pupil of Francesco Cupani) on the orders of the Prince of Cattolica, and/or some of his collaborators (or successors). The report of exchanges of plants with William Sherard, the particular composition of the collection and the documented knowledge of the international literature allow us to place the herbarium in the context of the intense scientific activity that took place in Sicily even after the deaths of Paolo Boccone and Cupani, two important pre-Linnaean Sicilian botanists.